Effect of Surface Modification of Silica Nanoparticles with Thiol group on the Shear Thickening Behaviors of the Suspensions of Silica Nanoparticles in polyethylene glycol (PEG). Issue 1 (1st February 2022) - Sharma, Shuchi; Kumar Walia, Yogesh; Grover, Gunjan; Sanjeev, Verma K.
Abstract: The Fine-tuning of Shear Thickening Fluids (STFs) by surface modification of silica particles has fascinated scientist's interest worldwide as it results in performance enhancement of STF based on armor systems. In the current study, surface modified Silica nanoparticles (average diameter of 600 nm) possess thiol functional groups which were attained through a reaction with 3-mercaptopropyl-trimethoxysilane in absolute ethanol at 90 °C. Shear thickening fluid of Thiol functionalized Silica nanoparticles were prepared by sonochemical method in polyethylene glycol (PEG-200). The rheological parameters of STFs (modified and unmodified silica Nano particles) were measured using Rheometer MCR 52, Anton Par, Germany. The shear thickening behavior of thiol-based STF shows shear thickening at a higher shear rate compared to only silica-based STF with the decrease in viscosity maximum.